Cross-sectional imaging in patients with primary sclerosing cholangitis: Single time-point liver or spleen volume is associated with survival. Issue 132 (November 2020) - Khoshpouri, Pegah; Ghadimi, Maryam; Rezvani Habibabadi, Roya; Motaghi, Mina; Venkatesh, Bharath Ambale; Shaghaghi, Mohammadreza; Pandey, Ankur; Hazhirkarzar, Bita; Ameli, Sanaz; Ghasabeh, Mounes Aliyari; Pandey, Pallavi; Kamel, Ihab R.
Abstract: Aim: To evaluate the association between single time-point quantitative liver and spleen volumes in patients with PSC and transplant-free survival, independent of Mayo risk score. Materials and Methods: This HIPAA-compliant retrospective study included 165 PSC patients in a hospital. Total (T), and lobar (right [R], left [L], and caudate [C]) liver volumes and spleen volume (S) were measured. Adverse outcome was identified as being on liver transplantation list, transplantation or death (outcome 1), and transplantation or death (outcome 2). Cox-regression was performed to assess the predictive value of volumetric parameters to predict transplant-free survival with and without Mayo risk score. Stratified analysis by Mayo risk score categories was performed to assess the discriminative value of volumes in the model. Prediction models were developed dependent of Mayo score, based on patients demographics, lab values and volumetric measures for both defined outcomes. Kaplan-Meier curves were depicted for different liver and spleen volumes. P value <0.05 was considered statistically significant. Results: In this cohort (age 43 ± 17 years; 59 % men) 51 % of patients had adverse outcome. Cox-regression analysis demonstrated statistically significant association between values of T, L, R, C, S, L/T, and C/T and outcome 1; and also statistically significant association between values C, S, and C/T and outcome 2. Prediction models included age, INR, total bilirubin, AST, variceal bleeding, S, and C for outcome 1 and age, INR, total bilirubin, AST, variceal bleeding, and S for outcome 2. Conclusions: Based on our observational study, quantitative liver and spleen volumes may be associated with transplant-free survival in patients with PSC and may have the potential for predicting the outcome but this should be validated by randomized clinical trial studies.